Oxygen reduction reaction on thin-film Ag electrodes in alkaline solution. (1st December 2019) - Linge, Jonas Mart; Erikson, Heiki; Kasikov, Aarne; Rähn, Mihkel; Sammelselg, Väino; Tammeveski, Kaido
Abstract: Thin Ag films with nominal thicknesses from 0.5 to 10 nm deposited on a glassy carbon (GC) substrate were prepared by electron beam evaporation and the oxygen reduction reaction (ORR) on the Ag/GC electrodes in alkaline solution was studied employing the rotating disk electrode (RDE) technique. Transmission electron microscopy (TEM) was used to examine the surface morphology of Ag films and it was found that the average particle size for the thinnest film was about 5.5 nm. The Ag particle size increased with increasing the film thickness and for 5 nm film the silver particles merged to a uniform coating. Electrochemical testing showed that the thin-film Ag electrodes are efficient catalyst for oxygen reduction and peroxide reduction reactions. The electron transfer number was calculated to be slightly lower than four for thinnest Ag film and it was 4 for all the other films. Tafel analysis showed similar slope value for all thin-film Ag electrodes revealing that the rate-determining step does not change with the Ag film thickness. The electro-oxidation of Ag films and Pb underpotential deposition experiments were also conducted. Finally, Ag coatings were electrochemically stripped from the GC electrode to determine the mass of Ag on the substrate surface, which was in good agreement with the calculated value. The 1 nm Ag film showed the best utilisation of silver, as mass and specific activities for ORR were the highest for that coating. Nanostructured Ag electrodes might be promising catalysts for alkaline membrane fuel cells. Highlights: Thin Ag films were prepared by electron beam evaporation and tested for the ORR. The ORR on thin-film Ag electrodes follows a four-electron pathway in alkaline media. Mass activity and specific activity for oxygen reduction is dependent on Ag loading. Thin Ag films are remarkably active towards the hydrogen peroxide reduction reaction.